2014
DOI: 10.1186/preaccept-1739683221127290
|View full text |Cite
|
Sign up to set email alerts
|

FunSeq2: A framework for prioritizing noncoding regulatory variants in cancer

Abstract: Identification of noncoding drivers from thousands of somatic alterations in a typical tumor is a difficult and unsolved problem. We report a computational framework, FunSeq2, to annotate and prioritize these mutations. The framework combines an adjustable data context integrating large-scale genomics and cancer resources with a streamlined variant-prioritization pipeline. The pipeline has a weighted scoring system combining: inter-and intra-species conservation; loss-and gain-of-function events for transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
258
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(263 citation statements)
references
References 46 publications
5
258
0
Order By: Relevance
“…A total of 11,679 out of 25,765 variants were not linked to clinically characterized genes and formed a separate panel (see Table 2 for an overview, which includes the number of pathogenic variants in each panel). In addition, we assessed the performance of GAVIN in compared to 12 common in silico tools for pathogenicity prediction: MSC (using two different settings), CADD (using three different thresholds), SIFT [5], PolyPhen2 [15], PROVEAN [16], Condel [17], PON-P2 [18], PredictSNP2 [19], FATHMM-MKL [20], GWAVA [21], FunSeq [22], and DANN [23].…”
Section: Performance Benchmarkmentioning
confidence: 99%
“…A total of 11,679 out of 25,765 variants were not linked to clinically characterized genes and formed a separate panel (see Table 2 for an overview, which includes the number of pathogenic variants in each panel). In addition, we assessed the performance of GAVIN in compared to 12 common in silico tools for pathogenicity prediction: MSC (using two different settings), CADD (using three different thresholds), SIFT [5], PolyPhen2 [15], PROVEAN [16], Condel [17], PON-P2 [18], PredictSNP2 [19], FATHMM-MKL [20], GWAVA [21], FunSeq [22], and DANN [23].…”
Section: Performance Benchmarkmentioning
confidence: 99%
“…They were regarded as transcription noise in the human genome, due to their lack of capability of protein translation. Over the previous decade, an increasing amount of evidence has indicated that lncRNAs have a variety of roles in numerous physiological processes (19)(20)(21)(22)(23)(24)(25). Despite a lack of capability of encoding proteins, lncRNAs may function through regulating gene expression at various levels, including chromatin architecture, transcription, RNA splicing, and protein translation and turnover (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of CADD as a support vector machine has successfully differentiated 14.7 million high-frequency human-derived alleles from 14.7 million simulated variants (18). Fu et al (19) developed a computational framework, FunSeq2, which processed large-scale genomics (including 1000 Genomes and ENCODE data) and cancer resources, and combined a high-throughput variant prioritization pipeline to annotate and prioritize somatic alterations, particularly regulatory non-coding mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Variants are scored by combining inter-and intra-species conservation, loss-and gain-of-function events for transcription-factor binding, enhancer-gene linkages and network centrality, and per-element recurrence across samples (13). Kircher et al (11) contrasted the annotations of fixed or nearly-fixed derived alleles in humans with those of simulated variants and developed combined annotation-dependent depletion (CADD).…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al (13) reported a computational framework, FunSeq2, that combines an adjustable data context integrating large-scale genomics, such as 1000 Genomes and ENCODE data, and cancer resources with a weighted scoring system. Variants are scored by combining inter-and intra-species conservation, loss-and gain-of-function events for transcription-factor binding, enhancer-gene linkages and network centrality, and per-element recurrence across samples (13).…”
Section: Introductionmentioning
confidence: 99%